PENERAPAN MODEL PEMBELAJARAN INKUIRI DENGAN METODE PICTORIAL RIDDLE TERHADAP HASIL BELAJAR PADA MATERI HUKUM GAS IDEAL DI SMA N 1 LIKUPANG - Mongan, Veronika Yohana; Silangen, Patricia Mardiana; Umboh, Sixtus Iwan (Charm Sains: Jurnal Pendidikan Fisika, 2024)
This study aims to determine how the application of inquiry learning model with pictorial riddle method on learning outcomes on ideal gas law material at SMA Negeri 1 Likupang. The method used in this research is quantitative method, with the research design is One Group Pretest-Posttest. The sample in this study was class XI MIA 1 which amounted to 20 students. Assessment data was collected using a test instrument in the form of a description. The average pretest score was 33.50 and the average posttest score was 85.25, the results of the data processing showed an increase. The results of the N-Gain Test obtained an N-Gain score of 0.8438 which indicates that there is an increase in student learning outcomes in the high category with a percentage of 84.38%. Based on the results of this study, it can be concluded that the pictorial riddle method of inquiry learning model can improve students' cognitive learning outcomes seen from the results of pretest and posttest data analysis using the N-Gain test, there are 18 students in the high category and 2 students with N-Gain scores in the medium category. With a percentage of 90% of students in the high category and 10% of students in the medium category. Then obtained the value of Sig. (2-tailed) is 0.000 <0.05 so it can be concluded that the application of the inquiry learning model with the pictorial riddle method can improve the learning outcomes of students in class XI MIA 1 even semester of SMA N 1 Likupang